Intravascular lithotripsy followed by angioplasty and stenting for severely calcified carotid artery stenosis: technical note and case series - Mitchell, Macy; Verhey, Leonard H.; Taylor, Naveen; Sewell, Andrea; Orozco, Andres Restrepo; Mazaris, Paul (Frontiers in Neurology, 2025)
PurposeIn patients with circumferential heavily calcified carotid stenosis, conventional carotid artery stenting (CAS) has its limitations, and carotid endarterectomy may be contraindicated. Intravascular lithotripsy (IVL) as an adjunct to CAS may be well suited for this subset of patients. We provide a technical report and series of five patients with severe, calcified carotid stenosis who underwent adjunctive IVL with CAS at our tertiary center.MethodsAll patients who underwent CAS with adjunctive IVL for severe carotid calcific stenosis at our center were included. All data were extracted from the electronic medical record and the departmental database. Data were synthesized in accordance with Preferred Reporting of Case Series in Surgery (PROCESS) guidelines.ResultsFive patients underwent CAS with adjunctive IVL for severe carotid stenosis between November 2022 and August 2024. The mean age at time of the procedure was 78.8 (SD 4.9); 80% were male. Patients presented with symptomatic stenosis, ranging from 50 to >95%. Symptoms included visual deficits (60%), hemiparesis (40%), facial droop (40%), and dysarthria (40%). All patients underwent post-procedural duplex ultrasound, which demonstrated resolution or significant reduction of stenosis. There were no clinical thromboembolic events. All patients have been followed in our comprehensive stroke program. Two patients died from causes unrelated to the procedure.ConclusionAdjunctive intravascular lithotripsy in patients with severe, circumferential calcified stenosis is a novel technique that has shown promising preliminary results. This application of intravascular lithotripsy warrants further investigation.